A review on: Pulsatile drug delivery system - Deshmukh, Jyotsana K.; Sable, Vidya (International Journal of Pharmacological Research, 2020)
In present time advancement are going on to develop modified dosage form i.e. sustain release, controlled release and extended release dosage form formulation to improve the therapeutic treatment, to improve patient convenience and compliance toward drug therapy. The recent studies, it was found that number of normal body function and disease condition show the chronobiological behavior. It was found that occurrence of diseases like asthma, peptic ulcers, cardiovascular diseases, diabetes mellitus, attention deficit syndrome in children, etc. Pulsatile drugs delivery systems are gaining lots of importance because it provides the delivery of drug at specific time, at specific amount and at specific site. Various systems like capsular, osmotic, single and multiple unit systems that is modulated by soluble or erodible polymer coatings, Rupturable membranes are available in market.pulsatile drug delivery systems have the potential to bring new developments in the therapy of various diseases.